Influência de técnicas de moldagem e de dois vazamentos na precisão dimensional de modelos de gesso e adaptação marginal de infraestruturas CAD/CAM em Y-TZP - Messias, Aion Mangino [UNESP] (2015)
This study conducted laboratory analysis of dental casts' accuracy obtained from different impression techniques and two castings, as well as measure the cervical marginal fit of zirconia infrastructures on dental preparations played in these models. Master model was used, with crown preparations in the teeth 14, 16, 21 and 25, on which zirconia infrastructures were made by CAD/CAM technology. For each impression technique full molds (n=15) were obtained by a single calibration operator with stock tray and polyvinylsiloxane: (T1) simultaneous mixture; (T2) reline - relief with PVC film and (T3) reline - relief with small movement of the tray. After mold removal, it was expected 120 min to realize the first pouring (type IV gypsum). The second pouring was made after 120 min from the removal of the first cast. To measure the marginal adaptation of infrastructure was used stereomicroscope LEICA (50x). For the analysis of linear dimensional accuracy, the models were photographed and, from pre-defined points, linear lateral-side occlusal measurements (LL) and anteroposterior, right (RPA) and left (EPA), were performed (ImageJ). Measurements of mesiodistal dimensions (MD) and bucco-lingual (VL) of the preparations and interpreparos distance segment 14-16 were performed. After verification of distribution and homocedasticity data, statistical methods (α = 0.05) were used to assess the influence of the independent variables. In general, larger models generated fringe displacement in relation to the master model, irrespective of the time of pouring (1º ou 2º). After 1st. pouring, the simultaneous technique tended to have lower misfit values than other techniques. Aside from tooth MD dimension 21 simultaneous technique produced dimensions MD and BL similar to the master model. No differences in inter-preparation linear dimensions and the occlusal line...(Complete abstract electronic access below)